Ассоциация генов кальпаин-кальпастатиновой системы и параметров экстерьера животных абердин-ангусской породы - Лысенко, Н.Г.; Колесник, А.И.; Горайчук, И.В.; Рубан, С.Ю.; Федота, А.М. (Фактори експериментальної еволюції організмів, 2016)
Aim. Due to improvement of cattle breeding methods the aim of the study was to assess the relationship between exterior
parameters of Aberdeen-Angus and genes associated with meat tenderness – CAPN1 (calpain) and CAST (calpastatin).
Methods. Livestock valuation methods were used to measure the exterior parameters of the animals. Molecular genetic
analysis was performed by PCR-RFLP. Statistical testing of hypothesis of association between the studied genotypes and
exterior parameters was conducted using ANOVA and Pearson product-moment correlation coefficient at significance
levels of 0.05, 0.01 and 0.001. Results. Desirable (associated with meat tenderness) alleles C of CAPN1 and CAST genes
are associated with an increase chest (CAPN1) and muscle (CAST) size. G alleles of these genes are associated with a
better-balanced body. Conclusions. Selection directed to increase of the C alleles of CAPN1 and CAST frequency allows
to improve the meat quality accompanied by increasing of body parts with a high content of muscle tissue and muscles.
Keywords: Aberdeen-Angus breed, exterior parameters, single nucleotide polymorphism, calpain and calpastatin genes.